The Effect of Sales and Marketing Performance on Wedding Package Sales at Resort X - Kadek Mia Savitri; I Nengah Wirata; Nyoman Reni Ariasri (Journal of Indonesian Management, 2026)
Wedding package sales are an important source of revenue in the hospitality industry, particularly for hotels targeting the destination wedding market. Their success depends not only on the quality of products and services but also on the effectiveness of the Sales and Marketing Department. This study aims to analyze the influence of Sales and Marketing performance on wedding package sales at Resort X based on employee perceptions. A quantitative approach was employed using saturated sampling, involving all 15 employees of the Sales and Marketing Department. Data were collected through questionnaires and documentation and analyzed using validity and reliability tests, classical assumption tests, multiple linear regression, t-test, F-test, and the coefficient of determination (R²). The findings indicate that Sales and Marketing performance did not have a significant effect on the sales volume dimension, with an R² of 38.4%. However, it showed a significant relationship with the profit-generation dimension, with an R² of 92.8%, and with supporting company growth, with an R² of 63.6%. These results reflect employee perceptions rather than direct measurements of actual sales or profit. Given the small sample size of 15 respondents and the high R² value, particularly for profit generation, the findings should be interpreted cautiously. The study suggests that improving Sales and Marketing performance may contribute to perceived profitability and company growth, while sales volume may also be influenced by factors such as pricing, facility quality, and wedding venue attractiveness.